ONLINE DISTANCE LEARNING (ODL) AND STUDENTS’ SELF-ESTEEM BASED ON DIFFERENT GENDER PERSPECTIVES - Siti Syamira Mohd Ramli; Wan Nurashikin Mahmood; Hamnah Che Hamzah; Hasnizawati Hashim; Norulhuda Tajuddin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Online Distance Learning (ODL) has been implemented in universities for over two years. Despite advancements in technology, ODL has proven to be challenging for students, which indirectly affects their self-esteem, regardless of gender. Thus, the study aims to investigate students’ self-esteem and to examine any significant mean difference between gender and students’ self-esteem. A survey was conducted on 378 students, and SPSS 26.0 was used to analyse the hypotheses of the study. It was found that students’ self-esteem level during ODL is moderate. The findings also revealed no significant difference between gender and student perception on self-esteem. The findings are expected to benefit academicians, policymakers, and university management in enhancing ODL implementation and preparing them for future learning challenges.